Decolorization of azo dye in aquoeos solutions by ultraviolet irradiation of XeBr excilamp - N. I. Philippova; G. G. Matafonova; V. B. Batoev (Тонкие химические технологии)
The efficiency of decolorization of azo dye Direct Blue KM in aqueous solutions by ultraviolet irradiation of XeBr excilamp (282 nm) in the range of initial concentrations of hydrogen peroxide and pH values was studied. The optimum operation conditions were determined.